2021
DOI: 10.3892/ol.2021.13111
|View full text |Cite
|
Sign up to set email alerts
|

DCLK1 and its interaction partners: An effective therapeutic target for colorectal cancer (Review)

Abstract: Doublecortin-like kinase protein 1 (DCLK1) is a microtubule-associated protein with a C-terminal serine/threonine kinase domain. Its expression was first reported in radial glial cells, where it serves an essential role in early neurogenesis, and since then, other functions of the DCLK1 protein have also been identified. Initially considered to be a marker of quiescent gastrointestinal and pancreatic stem cells, DCLK1 has recently been identified in the gastrointestinal tract as a marker of tuft cells. It has … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 95 publications
(105 reference statements)
0
8
0
Order By: Relevance
“…The vast majority of these studies to date have focused on expression of DCLK1, which promotes tumor invasiveness, epithelial-to-mesenchymal transition (EMT), and metastasis (118,120,121). DCLK1 can drive numerous signaling cascades critical in EMT and is associated with negative clinical outcomes in cancer (122). Although an excellent marker for tuft cells in mice, DCLK1 alone is insufficient to infer tuft cell identity, particularly in humans (1).…”
Section: Injurymentioning
confidence: 99%
“…The vast majority of these studies to date have focused on expression of DCLK1, which promotes tumor invasiveness, epithelial-to-mesenchymal transition (EMT), and metastasis (118,120,121). DCLK1 can drive numerous signaling cascades critical in EMT and is associated with negative clinical outcomes in cancer (122). Although an excellent marker for tuft cells in mice, DCLK1 alone is insufficient to infer tuft cell identity, particularly in humans (1).…”
Section: Injurymentioning
confidence: 99%
“…Many studies have shown that the overexpression of DCLK1 in cancer cells results in induction of EMT, stemness and increased cell migration and invasion, which can be reversed with small molecules targeting the kinase domain of DCLK1 [ 31 , 34 , 35 , 46 , 47 , 126 ]. In addition, targeting DCLK1 with anti-DCLK1 monoclonal antibody (CBT-15) or siRNAs showed promising results in reducing tumor burden, cancer stemness, invasion, and metastasis [ 31 , 35 , 41 , 46 , 47 , 48 , 49 , 50 , 51 , 54 , 127 , 128 , 129 , 130 , 131 , 132 , 133 , 134 ]. It remains to be shown whether such anti-DCLK1 targeting approaches are equally effective in the context of the various DCLK1 missense mutations that promote tumorigenesis.…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that down-regulation of NR5A2 is linked to worse overall survival of CRC patients [ 57 ]. The DCLK1 gene is reported to be up-regulated and associated with metastasis and prognosis in CRC [ 58 ]. Cytoplasmic expression of DCLK1-S, a novel DCLK1 isoform, has been shown to be associated with tumor aggressiveness and worse disease-specific survival in CRC [ 59 ].…”
Section: Discussionmentioning
confidence: 99%